The role of the Human Rights Commission of Sierra Leone in promoting and protecting the right to freedom of expression and assembly - Fombad, Charles Manga (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.